Hypoxia-induced ebv-circLMP2A promotes angiogenesis in EBV-associated gastric carcinoma through the KHSRP/VHL/HIF1α/VEGFA pathway. (1st February 2022) - Du, Yu; Zhang, Jing-yue; Gong, Li-ping; Feng, Zhi-ying; Wang, Deyu; Pan, Yu-hang; Sun, Li-ping; Wen, Jing-yun; Chen, Gao-feng; Liang, Jing; Chen, Jian-ning; Shao, Chun-kui
Abstract: EBV-encoded circular RNA LMP2A (ebv-circLMP2A) was found to be expressed in EBV-associated gastric carcinoma (EBVaGC) and associated with distant metastasis and poor prognosis. Angiogenesis is a key step in tumor invasion and metastasis and plays a crucial role in tumor progression. However, it is unclear whether and how ebv-circLMP2A is involved in angiogenesis. In this study, we showed that MVD, HIF1α, and VEGFA expression was increased in EBVaGC mouse xenografts with high expression of ebv-circLMP2A. The expression of ebv-circLMP2A was positively correlated with MVD, HIF1α, and VEGFA expression in clinical samples of EBVaGC. Knockdown of ebv-circLMP2A repressed tube formation and migration of HUVECs and decreased VEGFA and HIF1α expression in cancer cells under hypoxia, while ectopic expression of ebv-circLMP2A reversed these effects. Additionally, knockdown of HIF1α blocked the upregulation of ebv-circLMP2A by hypoxia, and ebv-circLMP2A interacted with KHSRP to enhance KHSRP-mediated decay of VHL mRNA, leading to the accumulation of HIF1α under hypoxia. There was a positive feedback loop between HIF1α and ebv-circLMP2A that promotes angiogenesis under hypoxia. ebv-circLMP2A was essential in regulating tumor angiogenesis in EBVaGC and might provide a valuable therapeutic target for EBVaGC. Highlights: ebv-circLMP2A is positively correlated with microvessel density, HIF1α, and VEGFA expression in EBVaGC. ebv-circLMP2A promotes tube formation and migration of HUVECs under hypoxia. ebv-circLMP2A promotes hypoxia-induced angiogenesis through KHSRP/VHL/HIF1α/VEGFA axis. HIF1α induces ebv-circLMP2A under hypoxic conditions.